Strategi Bhabinkamtibmas Menanggulangi Tindak Pidana Perjudian Desa Waro di Kecamatan Monta Kabupubaten Bima Nusa Tenggara Barat - Andriadin Andriadin; Erham Erham; Aman Ma'arij Aman Ma'arij (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
The phenomenon of gambling is considered normal by some people, even this act roots and develops just so, when there is no punishment from any law enforcement, it must become a disease that then destroys life. Gambling in the village of Waro involves children and young people, including the elderly. This condition will trigger the occurrence of disorganization and disintegration in the life of the community. This study examines gambling crimes in the village of Waro and also examines the strategies of gambling crime in the town of Monta in the Bima NTB. The method of research is empirical law research, which studies and examines the law in real terms.  The data used are primary and secondary data, such as results of interviews, documentation, observations, journals, books, previous research, and official documents.  The findings of the research show that, first, the criminal act of gambling in the village of Waro Prefecture in the Monta district of Bima is gambling card remi and gambling ball rolling both when there is a single organ event at night and during the day.  Secondly, the Bhabinkamtibmas strategy is to combat gambling crimes in Waro Village by conducting investigative, preventive, and repressive efforts.